2011
DOI: 10.1055/s-0031-1296412
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography–Mass Spectrometry Method for the Determination of Amlodipine in Human Plasma and its Application in a Bioequivalence Study

Abstract: A sensitive and selective liquid chromatographic-mass spectrometric (LC-MS) method for the determination of amlodipine (CAS 88150-42-9) in human plasma has been developed. Sample preparation was based on liquid-liquid extraction using NaOH and cyclohexane. Analytical determination was carried out on a C18 column interfaced with a single quadrupole mass spectrometer. Positive electrospray ionization was employed as the ionization source. The mobile phase was 10 mmol/L ammonium acetate solution-methanol (30:70, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…According to the reported data, our method appears sensitive enough for determination of atorvastatin and amlodipine in human plasma samples collected up to 24 or 96 h after administration. In addition, the sensitivity of the present assay was comparable to the reported studies for the individual determination of atorvastatin or amlodipine [9][10][11][12][13]. However, the sample pretreatment method employed in this study was much simpler than those of reported studies.…”
Section: Linearity and Sensitivitysupporting
confidence: 67%
See 1 more Smart Citation
“…According to the reported data, our method appears sensitive enough for determination of atorvastatin and amlodipine in human plasma samples collected up to 24 or 96 h after administration. In addition, the sensitivity of the present assay was comparable to the reported studies for the individual determination of atorvastatin or amlodipine [9][10][11][12][13]. However, the sample pretreatment method employed in this study was much simpler than those of reported studies.…”
Section: Linearity and Sensitivitysupporting
confidence: 67%
“…There were many studies available for the determination of amlodipine or atorvastatin in human plasma [9][10][11][12][13]. However, the study for the simultaneous determination of amlodipine and atorvastatin in human plasma was limited.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough literature review revealed that several LC-MS/MS methods have been published for the determination of AMD and ATL individually (for AMD [9][10][11][12][13][14][15][16] and for ATL [17]), or along with other drug(s) (ATL with other drugs [18][19][20][21][22] and AMD with other drugs [23][24][25][26][27]) in various biological matrices. It is important to develop a sensitive, rapid and reliable bioanalytical method for simultaneous quantitation of two or more drugs in combination therapy in human plasma.…”
mentioning
confidence: 99%
“…Several analytical methods have been reported for the determination of AML in pharmaceutical formulations and/or biological fluids. These methods include spectrophotometry [19][20][21], spectrofluorimetry [22,23], anodic stripping voltammetry [24,25], HPLC [26][27][28][29][30][31], HPTLC [32], capillary electrophoresis [33] and micellar electrokinetic chromatography [34].…”
Section: Introductionmentioning
confidence: 99%